Path Research on the Value Chain Reconfiguration of Manufacturing Enterprises Under Digital Transformation – A Case Study of B Company - Li, Yuanqin; Ding, Hao; Li, Ting (Frontiers in Psychology, 2022)
Emerging new digital technologies speed up the pace of the layout of the digital economy in various countries. As the main body of China's real economy, the manufacturing industry does not account for a high proportion of the digital economy, so the digital transformation of the manufacturing industry has become a hot topic. From the view of value chain reconfiguration, we selected B company as the case and introduced data from the closed-loop of collection, transmission, storage, processing and feedback into the analysis of the value chain. This study deeply studies the path of value chain reconfiguration of B company in the context of digital transformation. It finds that, under the impetus of digital transformation, B company has formed a new value chain form which is connected by data nodes in the value chain link, and completed the reconfiguration of value chain through value chain boost, value chain integration and value chain bond. On this basis, the study puts forward countermeasures and suggestions for the next phase of B company's digital transformation and the digital transformation of the manufacturing industry.